Walking as critical pedagogy - O'Neill, Maggie, author. aut Link Link Link
1 online resource
Keywords: Defining the principles and practices of walking as critical pedagogy, this book engages with social questions and challenges related to understandings of the Anthropocene.Through a series of chapters that operationalize walking as a form of participatory pedagogy, it explores issues including migration and borders, sustainability and climate change, gender and feminist thought, the labour market, crime and rehabilitation, and urban life and regeneration. Showing how walking enables us to learn creatively, convivially and critically on the move in city spaces, while thinking relationally, the authors demonstrate the importance of space, time and place: the layers of history embedded in the present, and the importance of active, embodied, participatory, collaborative, creative and place based learning.A pioneering approach to walking as a form of engagement and learning, Walking as Critical Pedagogy will appeal to researchers and students across the social sciences interested in new methods and research methodologies, and creative ways of teaching and learning about - and engaging with - major global issues in society.